Airflow Pattern in Broiler Houses as a Risk Factor for Growth of Enteric Pathogens - Myint, M.S.; Johnson, Y.J.; Branton, S.L.; Mallinson, E.T. (International Journal of Poultry Science, 2005)
Increased moisture in litter may create favorable conditions for multiplication of enteric pathogens. Areas of reduced air-flow within a broiler house are at increased risk of having excess litter moisture. A cross-sectional study was conducted to assess the association between airflow patterns within a poultry house and litter Salmonella and fecal coliform distribution. Five commercial broiler houses in two geographical regions of the USA were sampled. Both conventional and tunnel ventilated houses were represented in the sample. Airflow was not uniform throughout the houses sampled. Airflow at three feet (91.2cm) above the litter surface was greater than the airflow at three inches (7.6cm) above the litter surface. Across a 30 site sampling grid each house had at least 1 region where the airflow velocity was significantly reduced when compared to other regions within the house at the same height. The Friedman two-way analysis of variance found an association between regions of reduced airflow within a poultry house and regions of increased coliform and Salmonella contamination. Across all houses , there was a significant association between low air flow regions within the poultry house and fecal coliform counts in excess of the sample median (3.635 cfu /10 g of litter) (p=0.0073). Those litter samples with median fecal coliform counts in excess of 3.635 cfu/ 10 g of litter were 16 times more likely to come from a low air-flow region within the poultry house (95% CI 8.001, 31.994).